Evaluation of Multimedia Learning to Improve the Quality of Learning Using the Context, Input, Process, and Product (CIPP) Models - Zulkifli Zulkifli (research, training and philanthropy institution Natural Aceh, 2023)
Multimedia practicum is a learning that uses a computer to present animated navigation so that users can interact and communicate. To determine the quality of multimedia practicum, an evaluation of the learning is needed to see the effectiveness of the learning and the methods used. Using the Context, Input, Process, product evaluation (CIPP) model, Where the data collection technique uses questioner questionnaires that are distributed to students who have finished participating in multimedia practicum learning as many as 17 students, then also using observation and documentation after the data is collected, it is then analyzed statistically using the SPSS program so that it is obtained that the multimedia practicum in the informatics department at the Payakumbuh College of Technology is relevant to the needs of students, lecturers who teach by their fields and lecturers' teaching activities starting from the preparation, implementation, and closing of learning are in the sound and excellent category and the final score of multimedia practicum which gets A grade as much as 47%, B grade 47% and who gets a C grade as much as 6%. Meanwhile, those who get a D Value and a Fail Value of 0%. Based on the conclusions, it is known that the quality of learning within the scope of Context, Input, Process, and evaluation products is good so that the next multimedia practicum learning with the same method can be continued and improved so that the quality of learning remains good.